"Human Rights Are Not for Black Peoples": Understandings of International Human Rights Discourses by Young Adults in Tigray During War and Genocide - Pillay, Thashika; Gebremedhin, Fisseha Gidey; Baruwa, Ikeoluwapo; Tesfamariam, Micheal Abraham; Lalwani, Sanjay (Journal of Contemporary Issues in Education, 2025)
In November 2020, a war broke out between the Ethiopian federal government and the Tigray region in northern Ethiopia. This two-year period of extreme violence resulted in between 800,000 – 1 million Tegaru deaths, a communications blockade, sexual violence and starvation used as weapons of war, and an Ethiopian government imposed siege around Tigray to prevent entry of humanitarian aid. This study co-designed by three Tegaru researchers and one non-Tegaru researcher explored the experiences of young Tegaru adults, aged 18-25, during the early stages of the war. The findings in this paper are from semi-structured one-on-one interviews held in August/September 2022 with nine men and nine women and follow-up one-on-one interviews in January/February 2023, all of whom were living in the Tigray capital city of Mekelle. Participants shared their experiences related to the violence, siege and blockade imposed by the Ethiopian government during this period. Notably, most participants expressed strong condemnation of the actions taken by the international community, especially given the discrepancy as to how the international community responded to the Russia – Ukraine War which began in February 2022, 15 months after the conflict and genocide against Tigray began. Using the colonial matrix of power as a theoretical framework, this article shares Tegaru understandings of the international community’s response to the war and genocide in Tigray and Tegaru demands that international organizations and nation states put into action the human rights discourses they purport to support, demonstrating a desire for a universal practice of international human rights, one that does not privilege groups based on race or wealth. In not living up to these claims of the universality and neutrality of international human rights, international organizations and western nation states illustrated that human rights remains the domain of one particular subset of peoples, those with Eurocentric systems of knowing and being, who are seen as the true inheritors of the earth. These logics then destroy all other ways of knowing and being (Mignolo, 2007), and such acts become a production of invisibility wherein Tegaru lives are considered dispensable.